Size-specific abundance dynamics of Atlantic Bluefin Tuna in Canadian waters - Sosthene A.V. Akia; Alex Hanke; Daniel Duplisea (Fisheries Research, 2025)

Spatial and Temporal Size Distribution of Swordfish ( Xiphias gladius ) in the Atlantic Ocean: Implications for Conservation and Management - Daniela Rosa; Michael Schirripa; Kyle Gillespie; David Macías; Rodrigo Forselledo; Bruno Mourato; Mikihiko Kai; Freddy Arocha; Nan-Jay Su; Sven Kerwath; Laurent Bahou; Luigi Pappalardo; et al. (Reviews in Fisheries Science & Aquaculture, 2025)

Sea turtles in the Atlantic and Indian Oceans, a step towards understanding bycatch and management of these species in tuna fisheries - Andrés Domingo; José Carlos Baéz; Philip Miller; Denham Parker; María Lourdes Ramos; Philippe S. Sabarros; Craig Brown; Juan Antonio Camiñas; Rui Coelho; Rodrigo Forselledo; Fernando Niemeyer Fiedler; Bruno Giffoni; et al. (Biological Conservation, 2025)

Estimating age-at-maturity for individual Atlantic bluefin tuna (Thunnus thynnus) from back-calculated growth trajectories - Nathan D. Stewart; Kyle L. Wilson; Alex Hanke (Fisheries Research, 2024)

Unidirectional trans‐Atlantic gene flow and a mixed spawning area shape the genetic connectivity of Atlantic bluefin tuna - Natalia Díaz‐Arce; Pierre‐Alexandre Gagnaire; David E. Richardson; John F. Walter; Sophie Arnaud‐Haond; Jean‐Marc Fromentin; Deirdre Brophy; Molly Lutcavage; Piero Addis; Francisco Alemany; Robert Allman; Simeon Deguara; et al. (Molecular Ecology, 2024)
The commercially important Atlantic bluefin tuna ( Thunnus thynnus ), a large migratory fish, has experienced notable recovery aided by accurate resource assessment and effective fisheries management efforts. Traditionally, this species has been perceived as consisting of eastern and western populations, spawning respectively in the Mediterranean Sea and the Gulf of Mexico, with mixing occurring throughout the Atlantic. However, recent studies have challenged this assumption by revealing weak genetic differentiation and identifying a previously unknown spawning ground in the Slope Sea used by Atlantic bluefin tuna of uncertain origin. To further understand the current and past population structure and connectivity of Atlantic bluefin tuna, we have assembled a unique dataset including thousands of genome‐wide single‐nucleotide polymorphisms (SNPs) from 500 larvae, young of the year and spawning adult samples covering the three spawning grounds and including individuals of other Thunnus species. Our analyses support two weakly differentiated but demographically connected ancestral populations that interbreed in the Slope Sea. Moreover, we also identified signatures of introgression from albacore ( Thunnus alalunga ) into the Atlantic bluefin tuna genome, exhibiting varied frequencies across spawning areas, indicating strong gene flow from the Mediterranean Sea towards the Slope Sea. We hypothesize that the observed genetic differentiation may be attributed to increased gene flow caused by a recent intensification of westward migration by the eastern population, which could have implications for the genetic diversity and conservation of western populations. Future conservation efforts should consider these findings to address potential genetic homogenization in the species.

Atlantic bluefin tuna diet variability in the southern Gulf of St. Lawrence, Canada - François Turcotte; Alex Hanke; Jenni L. McDermid (Marine Environmental Research, 2023)

Timing of Increment Formation in Atlantic Bluefin Tuna (Thunnus thynnus) Otoliths - Enrique Rodriguez-Marin; Dheeraj Busawon; Patricia L. Luque; Isabel Castillo; Nathan Stewart; Kyne Krusic-Golub; Aida Parejo; Alex Hanke (Fishes, 2022)
Controversies remain regarding the periodicity, or seasonality, of otolith growth band formation, which directly influences a correct age determination of Atlantic bluefin tuna using this structure. The aim of this work was to apply marginal increment analysis and marginal edge analysis to determine the timing of band deposition. The index of completion was analyzed using general additive models to evaluate the importance of variables, such as month, age/size, and reader. Results indicate that the opaque band formation begins in June and is completed by the end of November. From the end of the year to the beginning of the following year, there is minimal marginal edge growth as the translucent band begins to form. The translucent zone then reaches a maximum development in May. The results obtained in this study provide evidence that the annulus formation in the otoliths of Atlantic bluefin tuna are completed later in the calendar year than previously thought. This would mean it is necessary to delay the date of the current July 1st adjustment criterion to November 30.

Environmental influences on A tlantic bluefin tuna ( Thunnus thynnus ) catch per unit effort in the southern G ulf of S t. L awrence - Angelia S. M. Vanderlaan; Alex R. Hanke; Joël Chassé; John D. Neilson (Fisheries Oceanography, 2014)
The A tlantic bluefin tuna ( T hunnus thynnus ) population in the western A tlantic supports substantial commercial and recreational fisheries. Despite quota establishment and management under the auspices of the International Commission for the Conservation of A tlantic T unas, only small increases in population growth have been estimated. In contrast to other western bluefin tuna fisheries indices, contemporary estimates of catch per unit effort ( CPUE ) in the southern G ulf of S t. L awrence have increased rapidly and are at record highs. This area is characterized by the Cold Intermediate Layer ( CIL ) that is defined by waters in situ environmental variables on the bluefin tuna fishery CPUE using delta‐lognormal modelling and relatively extensive and consistent oceanographic survey data, as well as dockside monitoring and mandatory logbook data associated with the fishery. Although there is considerable spatial and temporal variation of water mass characteristics, the amount of available habitat in the southern G ulf of S t. L awrence (assuming a > 3°C thermal ambit) for bluefin tuna has been increasing. The percentage of the water column occupied by the CIL was a significant environmental variable in the standardization of CPUE estimates. There was also a negative relationship between the spatial extents of the CIL and the fishery. Properties of the CIL account for variation in the bluefin tuna CPUE and may be a factor in determining the amount of available feeding habitat for bluefin tuna in the southern G ulf of S t. L awrence.